Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1161/jaha.115.003085
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C Predicts Incident Cardiovascular Disease in Twins

Abstract: BackgroundCystatin C is associated with both renal function and atherosclerotic cardiovascular disease (ASCVD). We have previously shown a genetic correlation between cystatin C and prevalent ASCVD. The objective of this article is to study whether variation in cystatin C or creatinine predicts incident ASCVD when controlled for genetic factors.Methods and ResultsThe predictive value of cystatin C and creatinine for incident ASCVD was studied in 11 402 Swedish twins, free of CVD at baseline, in an adjusted Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The largest body of work, however, has been examining the association between cystatin C and cardiovascular disease. Rising cystatin C values are associated with the development and progression of cardiovascular disease (CVD), independent of renal function and other cardiovascular risk factors [65][66][67][68][69][70][71]. Cystatin C also has been found to hold prognostic value for procedure related outcomes [72][73][74][75][76], critical illness [44,77], and CVD and all cause mortality in both CVD patients [78][79][80][81] and the general population [82].…”
Section: Cystatin C For Risk Prediction In Ckdmentioning
confidence: 99%
“…The largest body of work, however, has been examining the association between cystatin C and cardiovascular disease. Rising cystatin C values are associated with the development and progression of cardiovascular disease (CVD), independent of renal function and other cardiovascular risk factors [65][66][67][68][69][70][71]. Cystatin C also has been found to hold prognostic value for procedure related outcomes [72][73][74][75][76], critical illness [44,77], and CVD and all cause mortality in both CVD patients [78][79][80][81] and the general population [82].…”
Section: Cystatin C For Risk Prediction In Ckdmentioning
confidence: 99%
“…Recent studies have shown that serum cystatin C (Cys-C) is closely associated with CAD [ 3 , 4 ]. Cys-C was an independent predictor of cardiac events, and could be an indicator of CAD severity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 It has been reported to be a useful biomarker for the detection of preeclampsia. 16 , 17 Available studies have demonstrated that impaired renal function, as assessed by serum levels of creatinine 10 , 18 , 19 , 20 or CysC, 10 , 18 , 21 , 22 , 23 , 24 , 25 predicts future CVD. However, most of these studies were conducted in nonpregnant older women, and limited data are available to address the role of these renal biomarkers measured shortly after delivery on severe maternal CVD morbidities later in life, individually and in combination with pregnancy complications.…”
mentioning
confidence: 99%